Genotype Differences in Sensitivity to the Anticonvulsant Effect of the Synthetic Neurosteroid Ganaxolone during Chronic Ethanol Withdrawal. (15th January 2019) - Nipper, Michelle A.; Jensen, Jeremiah P.; Helms, Melinda L.; Ford, Matthew M.; Crabbe, John C.; Rossi, David J.; Finn, Deborah A.
Highlights: Potent anticonvulsant effect of synthetic neurosteroid ganaxolone in control mice. Resistance to ganaxolone during ethanol withdrawal in Withdrawal Seizure-Prone mice. Sensitivity to ganaxolone during ethanol withdrawal in DBA/2J mice. Similar ganaxolone sensitivity in control males and females and during withdrawal. Ganaxolone will be a useful treatment of ethanol withdrawal-induced seizures. Abstract: Sensitivity to anticonvulsant effects of the γ-aminobutyric acidA receptor-active neurosteroid allopregnanolone (ALLO) during ethanol withdrawal varies across genotypes, with high sensitivity in genotypes with mild withdrawal and low sensitivity in genotypes with high withdrawal. The present studies determined whether the resistance to ALLO during withdrawal in mouse genotypes with high handling-induced convulsions (HICs) during withdrawal could be overcome with use of ganaxolone (GAN), the metabolically stable derivative of ALLO. In separate studies, male and female Withdrawal Seizure-Prone (WSP-1) and DBA/2J (D2) mice were exposed to air (controls) or 72-h ethanol vapor and then were scored for HICs during withdrawal (hourly for the first 12 h, then at hours 24 and 25). After the HIC scoring at hours 5 and 9, mice were injected with 10 mg/kg GAN or vehicle. Area under the HIC curve (AUC) for hours 5–12 was analyzed. In control WSP-1 mice, GAN significantly reduced AUC by 52% (males) and 63% (females), with effects that were absent or substantially reduced during withdrawal. In contrast, GAN significantly reduced AUC in both control and ethanol-withdrawing male and female D2 mice. AUC was decreased by 81% (males) and 70% (females) in controls and by 35% (males) and 21% (females) during withdrawal. The significant anticonvulsant effect of GAN during withdrawal in D2 but not WSP-1 mice suggests that different mechanisms may contribute to ALLO insensitivity during withdrawal in these two genotypes. Importantly, the results in D2 mice suggest that GAN may be a useful treatment for ethanol withdrawal-induced seizures.